2021
DOI: 10.1016/j.joca.2021.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Are changes in meniscus volume and extrusion associated to knee osteoarthritis development? A structural equation model

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Three MRI-based predictors were associated with the meniscus in the predictive model of radiographic progression. Medial meniscus extrusion has been reported to be related to the incidence of radiographic knee OA (defined as KLG ≥ 2) in middle-aged overweight and obese women over 30 months follow-up [ 8 ]. An MRI study showed substantial medial meniscus extrusion (> 3 mm) correlated with severe meniscal degeneration, extensive tear, complex tear, large radial tear, and tear involving the meniscal root [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three MRI-based predictors were associated with the meniscus in the predictive model of radiographic progression. Medial meniscus extrusion has been reported to be related to the incidence of radiographic knee OA (defined as KLG ≥ 2) in middle-aged overweight and obese women over 30 months follow-up [ 8 ]. An MRI study showed substantial medial meniscus extrusion (> 3 mm) correlated with severe meniscal degeneration, extensive tear, complex tear, large radial tear, and tear involving the meniscal root [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by data from a guineapig model, where meniscal hypertrophy was tied to cartilage damage after ACL injury ( 32 ). Although little to no data exist regarding meniscal size changes after ACL injury in humans, larger meniscus volume in middle-aged women was tied to later development of structural OA ( 33 ). While it is common to evaluate meniscal tears after ACL injury, meniscal size, independent of the presence of injury, is often overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…After segmentation of various joint structures, for example the articular cartilage, bones and menisci, their morphometric features (e.g., thickness, area, volume, or shape) can be determined. Change of these measures have been linked to OA onset and progression [ 39 42 ]. Here, the segmentation forms a challenge because it is laborious if performed manually, in particular for 3D datasets.…”
Section: Classification Of Early-stage Oa and The Role Of Imagingmentioning
confidence: 99%